RESESI SEKS : ANTARA KEBEBASAN INDIVIDU DAN HUKUM ISLAM - Asmita, Sri; Fathimah, Ema (STIT Sunan Giri Bima, 2024)
Developed countries, a sexual recession has become a new trend among the community, manifested in the form of concerns about family responsibilities. The high regard for the legality of marriage by all religions is gradually shifting with the times. The institution of marriage is considered incompatible with the current lifestyle of society, especially in some non-Muslim majority developed countries. This article aims to examine and analyze how a sexual recession can occur, and what are the factors and implications of the sexual recession in the era of disruption. This research is qualitative and descriptive, collecting data through library research and observing phenomena by obtaining evidence through the internet and various social media platforms such as YouTube, Instagram, Google, and others. The article shows that sexual recession is prevalent in some developed countries such as Japan, the United States, South Korea, China, and so on. This is due to a decline in interest in sex, marriage, and having children. Sex and religion, especially Islamic law, seem to act as constraints on individual freedom, leading to a decline in population from all aspects of life This serves as evidence that the sexual recession in some countries, especially developed ones, is heavily influenced by religious dogma and free association. Therefore, a study is needed that confronts the epistemology of religious dogma, especially when confronted with Islamic law and individual freedom within marriage.